1997
DOI: 10.2466/pr0.1997.80.3c.1211
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression: A Breakdown in Sense of Coherence?

Abstract: The relationship between major depression and the salutogenic construct of sense of coherence was investigated. The Sense of Coherence scale and the Beck Depression Inventory were administered to 50 patients diagnosed with major depressive disorder and to 50 control subjects. Significant negative correlations were found between scores on Depression and total scores on the Sense of Coherence scale as well as all three of its subscales (Comprehensibility, Manageability, and Meaningfulness). A significant positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 16 publications
7
67
0
1
Order By: Relevance
“…The current finding also confirms previous studies showing that sense of coherence is an important mediator between adversity, such as perceived racial discrimination, and psychological well-being. As Carstens and Spangenberg (1997) asserted, the current study provided additional support for understanding depression as a breakdown in sense of coherence.…”
Section: Standardized B Coefficients Of Variablessupporting
confidence: 64%
“…The current finding also confirms previous studies showing that sense of coherence is an important mediator between adversity, such as perceived racial discrimination, and psychological well-being. As Carstens and Spangenberg (1997) asserted, the current study provided additional support for understanding depression as a breakdown in sense of coherence.…”
Section: Standardized B Coefficients Of Variablessupporting
confidence: 64%
“…For example, the BDI has been shown to significantly correlate with other measures of depression and clinicians' ratings of depression, indicating evidence of concurrent validity (Corcoran & Fischer, 1987). In addition, several studies have provided reliability and validity estimates for the BDI used in Black South African samples (e.g., Cartens & Spangenberg, 1997;Naidoo & Pillay, 1994;Pillay & Sargent, 1999;Westaway & Wolmarans, 1992). In our current study, we found similar means and standard deviations for the BDI.…”
Section: Instrumentsmentioning
confidence: 99%
“…Some researchers (for example, Carstens & Spangenberg, 1997:1211-1220 argue that the PIL test (Crumbaugh & Maholick, 1981:1-15) indirectly measures depression. The PIL and the meaningfulness subscale of the SOC scale were shown to be very similar in this study, so their possible links to depression should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that meaning in life motivates individuals and contributes to their overall health is a pivotal idea in psychology, a proposition offered by Viktor Frankl (1905-1997. He argues that, regardless of one's circumstances, life has meaning and that every individual has the capacity and responsibility to find meaning in life, even during times of stress and crisis (Frankl, 1992:1-165).…”
Section: Gebruik Die "Adolescent Coping Scale" Is Gebruik Om Die Opgmentioning
confidence: 99%